Dynamic signature for tumble turn performance in swimming - Slawson, S.; Conway, P.; Justham, L.; Le Sage, T.; West, A. (Procedia Engineering, 2010)
The primary aim of work presented within this paper was to establish characteristics seen in acceleration which pertained to phases of the tumble turn. To achieve this, a subject performed a 400m freestyle swim as part of their normal training session during which time they were asked to wear a wireless accelerometer in the small of their back. In addition video data of the turns was captured using a fixed underwater camera. Acceleration data was aligned with video to enable turning phases to be distinguished to facilitate more comprehensive analysis of the turn.